{Premenstrual dysphoric disorder: A critical review of its phenomenology, etiology, treatment and clinical status} - Alevizou, F.; Vousoura, E.; Leonardou, A. (Current Women's Health Reviews, 2018)
© 2018 Bentham Science Publishers. Background: Premenstrual Dysphoric Disorder (PMDD) is a newly recognized diagnostic entity in the DSM-5, characterized by intense mood and cognitive fluctuations accompanied by distressing physical symptoms. PMDD symptoms typically arise after ovulation and gradually resolve after the onset of menstruation. With an estimated prevalence of 3-8% in the general female population, PMDD is a chronic and impairing disorder that affects significantly women's quality of life and everyday functioning. Objective: The aim of this article is to review the existing literature on biological, genetic and psychological etiological factors in PMDD and to discuss corresponding treatment considerations. Results: Fluctuations in the functions of sex hormones, serotonin and GABA neurotransmitters, as well as personality traits related to stress and vulnerability to negative effect are implicated in the development of PMDD. Available evidence-based treatments include a number of hormonal therapies and antidepressant medications, while there is accumulating evidence for the clinical utility of psychotherapeutic interventions. Controversies in the diagnostic validity of PMDD mainly concern the asserted social constructiveness of the disorder and the difficulty to validly distinguish PMDD from other mood disorders with similar symptomatology. Conclusion: Controversies pertaining to the clinical nature and taxonomy of PMDD are highlighted and recommendations are offered, focusing on the need to identify biomarkers for PMDD and to investigate possible efficacy of non-pharmacological, psychotherapeutic interventions to address PMDD.
Keywords: Dsm-5; Epidemiology; Pmdd; Premenstrual dysphoric disorder; Premenstrual syndrome; taxonomy; Treatment; Women's mental health